HUBUNGAN KONSUMSI KOPI DAN MEROKOK TERHADAP KUALITAS TIDUR PADA PENGUNJUNG COFFEE SHOP DI KOTA SAMARINDA : THE RELATIONSHIP BETWEEN COFFEE CONSUMPTION AND SMOKING AND SLEEP QUALITY OF COFFEE SHOP VISITORS IN SAMARINDA CITY - Puspa, Devi Renita; Isnuwardana, Ronny; Ramadhany, Candra (ITKES Wiyata Husada Samarinda, 2025)
Sleep may have an important role in health, but many people experience sleep disturbances both in terms of duration and quality which are influenced by many factors such as changes in lifestyle and social needs. Coffee consumption is becoming a trend and is linked to sleep disorders because it contains caffeine. Apart from that, smoking also affects sleep quality because nicotine levels affect the central nervous system. The aim of this research is to determine the relationship between coffee consumption and smoking on sleep quality among coffee shop visitors in the city of Samarinda. The research design used in this study was cross sectional. The sample for this research is coffee shop visitors. The sampling technique used in this research was Accidental Sampling. The amount of data used in this research was 136 data. From the results of bivariate analysis using Fisher's exact test and chi-square test, the hypothesis test results for the variable coffee consumption and sleep quality (p=0.327) and cigarette consumption and sleep quality (p=0.004) were obtained. The conclusion of this study is that there is a relationship between cigarette consumption and sleep quality and there is no relationship between coffee consumption and sleep quality.